Correlation of Interleukin-33/ST2 Receptor and Liver Fibrosis Progression in Biliary Atresia Patients - Liu, Jia; Yang, YiFan; Zheng, Chao; Chen, Gong; Shen, Zhen; Zheng, Shan; Dong, Rui (Frontiers in Pediatrics, 2019)
Background/Aims: Biliary Atresia (BA) is a devastating pediatric liver disease and characterized by aggressive liver fibrosis progression. The Interleukin-33 (IL-33)/ST2 receptor signaling axis has been demonstrated to be involved in several autoimmune and liver diseases. Since immune dysregulation is a contributor to BA pathogenesis, we aimed to investigate the role of IL-33/ST2 receptor in the progression of liver fibrosis in BA patients. Materials and Methods: The study included 36 BA patients (18 good- and 18 poor-prognosis BA patients); and 8 cholestasis infants as the control group. Patients’ information and clinical data were retrospectively collected and compared. Liver fibrosis stage was determined by Masson’s trichrome staining. Gene expression levels of IL-33, ST2 receptor and TFG-β1 were detected by quantitative real-time PCR. MC count, IL-33, TGF-β1 and Interleukin-13 (IL-13) expressions were evaluated by immunohistochemistry. Serum IL-33 expression level was detected by enzyme-linked immunosorbent assay. Co-expression of MC and ST2 receptor was detected by immunofluorescence. In vitro mast cell was cultured with IL-33 stimulation, and ST2 receptor and TGF-β1 expressions were detected. Results: Compared with cholestasis control, BA patients had significantly higher GGT level and Masson score. Expression levels of IL-33, TGF-β1 and IL-13 were significantly increased in BA patients compared to control group, especially in poor-prognosis BA patients. Co-expression of ST2 receptor and MC was found in BA liver tissues. The MC count was markedly higher in BA patients especially in poor-prognosis subgroup. Serum IL-33 level was significantly elevated in poor-prognosis BA patients and related to a higher Masson score. In vitro mast cell culture exhibited significant upregulation of ST2 receptor and TGF-β1 mRNA expression after IL-33 stimulation . Conclusions: IL-33/ST2 receptor signaling axis is correlated with liver fibrosis progression in BA patients, and mast cells participates in this process. These indicate potential prognostic evaluation factors for BA patients and can help in the postoperative management to achieve better long-term prognosis in BA patients.